Novel Magnesium Based Materials: Are They Reliable Drone Construction Materials? A Mini Review - Höche, Daniel; Weber, Wolfgang E.; Gazenbiller, Eugen; Gavras, Sarkis; Hort, Norbert; Dieringa, Hajo (Frontiers in Materials, 2021)
Novel magnesium-based materials are ideal candidates for use in future aviation vehicles because they are extremely light and can therefore significantly increase the range of these vehicles. They show very good castability, are easy to machine and can be shaped into profiles or forgings to be used as components for next generation aerial vehicle construction. In the case of a large number of identical components, high-pressure die casting of magnesium alloys is clearly superior to high-pressure die casting of aluminium alloys. In addition, the die filling times for magnesium high-pressure die casting are approximately 30 % shorter. There are cost-effective novel die casting alloys, besides AZ91 or AM50/60 such as DieMag633 or MRI230D, which show very good specific strength at room and elevated temperatures. In the case of magnesium-based wrought alloys, the choice is smaller, a typical representative of these materials is AZ31, but some new alloys based on Mg-Zn-Ca are currently being developed which show improved formability. However, magnesium alloys are susceptible to environmental influences, which can be eliminated by suitable coatings. Novel corrosion protection concepts for classical aerial vehicles currently under development might suitable but may need adaption to the construction constraints or to vehicle dependent exposure scenarios. Within this mini-review a paradigm change due to utilisation of new magnesium materials as drone construction material is briefly introduced and future fields of applications within next-generation aerial vehicles, manned or unmanned, are discussed. Possible research topics will be addressed